Cymbeline - Shakespeare, William, 1564-1616.; Nosworthy, J. M. (London : AS, 2000)
Presents an annotated edition of Shakespeare's romantic play of intrigue and misadventure; and includes detailed notes, a full introduction discussing the critical and historical background of the play, and appendices presenting sources and relevant extracts.
Includes bibliographical references.
Adult
Keywords: Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616.; Britons -- Kings and rulers -- Drama; Fathers and daughters -- Great Britain -- Drama; Married people -- Great Britain -- Drama; English drama; Father-daughter relationship -- Drama; Historical drama; Married people -- Great Britain -- Drama; Great Britain -- History -- Roman period, 55 B.C.-449 A.D -- Drama; Great Britain -- History -- Drama; Great Britain -- Kings and rulers -- Drama